Special teaching in higher education : successful strategies for access and inclusion - Powell, Stuart (Kogan Page, 2003)
Covering the Special Educational Needs and Disability Act (SENDA), this book addresses the learning needs of impaired and disabled students. It suggests effective responses for those designing and delivering the curriculum and discusses flexible teaching strategies. An essential purchase for any education professionals wanting to implement best practice when catering for those with particular needs - whether lecturers, course developers, course leaders or learning and teaching interest groups.